Application of blockchain technology in shipping industry - Kedaritis, Andreas (Department of Commerce Finance and Shipping, 2020)
This thesis with title “Application of Blockchain Technology in Shipping Industry” written by Andreas Kedaritis, student of Cyprus University of technology in the department of Commerce, Finance and Shipping under the supervision of Dr. Isabella Karasamani. The purpose of the thesis is to analyze if blockchain technology can improve the performance of Shipping companies and in what procedures can be most useful. Also, examines if that technology can eliminate the problem of cyber-attacks and data thefts, that costs to companies millions every year. In the paper will be explained how blockchain works and in what ways can be applied and developed by the shipping industry. The research shows that blockchain can benefit the shipping industry in many different factors by minimizing the expenses and improving the efficiency of companies, as well as, that there are some challenges that makes the implementation of blockchain technology a complexity matter. Concerning the cybersecurity for companies, turns out that blockchain technology can really be useful and make cyber-attacks not such a bid deal. Blockchain turns out that is a crucial new technology that can unfold maritime from being a traditionally industry to a more innovative and technologically advanced industry.
Keywords: Blockchain technology